Use of data linkage and LEO data in the evaluation of the Basic Income Pilot in Wales - Fallick, Sam; Helliwell, Kathryn (International Journal of Population Data Science, 2026)
The presentation will outline the data linkage methodology underpinning the evaluation of Wales’ Basic Income Pilot (BIP), with a particular focus on connecting BIP participant data to the Longitudinal Education Outcomes (LEO) datasets. The BIP is a landmark pilot providing care-leavers with a monthly income for two years. The evaluation aims to assess the education and labour market outcomes of BIP recipients compared to their non-recipient peers. The LEO dataset integrates multiple educational datasets, as well as employment and benefits data from the Department for Work and Pensions (DWP) and His Majesty’s Revenue and Customs (HMRC) providing a comprehensive view of education and employment outcomes. To facilitate this analysis, a secure and privacy-conscious linkage process has been designed. The BIP monitoring database, containing personal identifiers for pilot recipients, will be matched to the constituent education datasets held within LEO, using select data points. The linkage will take place within the Welsh Government, which already holds all the relevant datasets. This internal linkage avoids the need to transfer any personal data externally, minimising privacy risks and ensuring compliance with data governance protocols. Following linkage, the evaluation contractors will receive an anonymised, flagged dataset via the Welsh Government Secure e-Research Platform, containing the LEO data relevant to the BIP recipients. Contractors will not be able to identify individuals, preserving participant confidentiality. Access to the data is further restricted to accredited researchers. This approach demonstrates a robust, ethical model for linking administrative data in policy evaluation, balancing analytical needs with stringent privacy protections.